2020
DOI: 10.21203/rs.3.rs-74258/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between an Increase in Blood Urea Nitrogen at 24 Hours and Worse Outcomes in COVID-19 Pneumonia

Abstract: Background and objectives: The dynamic change of blood urea nitrogen (BUN) have been proved to be related to the worse outcomes in various diseases such as pulmonary embolism, acute pancreatitis and acute nonvariceal upper GI bleeding. In the present study, we aimed to identify the association between blood urea nitrogen (BUN) change and clinical outcomes in patients presenting with COVID-19 pneumonia.Methods: This is a retrospective study conducted in the Huoshenshan hospital. Patients with laboratory-confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“… 61 Histidine and lysine residues, often found in viral envelope proteins, play roles in the activation of serine proteases assisting viral entry to host cells. 62 , 63 RNA-seq analysis of upper airway samples identified that severe/fatal disease is associated with higher initial and increased subsequent expression of genes related to extracellular matrix formation and cell adhesion, including fibronectin. 64 , 65 These findings suggest a potential etiology for our plasma proteome results that demonstrated thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Histidine and lysine residues, often found in viral envelope proteins, play roles in the activation of serine proteases assisting viral entry to host cells. 62 , 63 RNA-seq analysis of upper airway samples identified that severe/fatal disease is associated with higher initial and increased subsequent expression of genes related to extracellular matrix formation and cell adhesion, including fibronectin. 64 , 65 These findings suggest a potential etiology for our plasma proteome results that demonstrated thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The urea and creatine level has been observed to be higher in COVID-19 patients, and these are related to kidney abnormalities/failure, (Cheng et al, 2020; Ye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Note that leukocytosis could also be related to bacterial infections, corticosteroids use, or age, and others unrelated to COVID-19 severity. The urea and creatine level has been observed to be higher in COVID-19 patients, and these are related to kidney abnormalities/failure, ( Cheng et al, 2020 , Ye et al, 2021 . A recent study indicated that SARS-Cov-2 infection of kidney was possible ( Jansen et al, 2022) .…”
Section: Discussionmentioning
confidence: 99%
“…The urea and creatine level has been observed to be higher in COVID-19 patients, and these are related to kidney abnormalities/failure, ( Cheng et al, 2020 , Ye et al, 2021 . A recent study indicated that SARS-Cov-2 infection of kidney was possible ( Jansen et al, 2022) .…”
Section: Discussionmentioning
confidence: 99%